2017
DOI: 10.1002/2017sw001719
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Thermospheric Density Profiles From EUV Solar Occultations Made by PROBA2 LYRA for Solar Cycle 24

Abstract: A new data set of summed neutral N2 and O number density profiles, spanning altitudes between 150 and 400 km, and observed during Northern Winter from 2010 to 2016 is presented. The neutral density profiles are derived from solar occultation measurements made by the 0.1–20 nm Zr channel on the Large Yield Radiometer (LYRA) instrument on board Project for Onboard Autonomy 2 (PROBA2). The climatology derived from the vertical profiles is consistent with that predicted by the NRLMSISE‐00 model, and the systematic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(63 citation statements)
references
References 27 publications
11
52
0
Order By: Relevance
“…Nevertheless, the uncertainties for LYRA are comparable to those shown for EUVM in Figure . Further, Thiemann, Dominique, et al () found better than 5% agreement with the LYRA measurements and predictions made by the NRLMSISE‐00 empirical model for Earth's thermospheric density (Picone et al, ), which has been independently characterized and validated by available thermospheric density measurements at the Earth. The good agreement between LYRA solar occultation observations and NRLMSISE‐00 predictions also serve to validate the EUVM‐SO observations given the similarities in the instruments and near identical retrieval algorithms.…”
Section: Density Retrieval Uncertaintymentioning
confidence: 89%
See 4 more Smart Citations
“…Nevertheless, the uncertainties for LYRA are comparable to those shown for EUVM in Figure . Further, Thiemann, Dominique, et al () found better than 5% agreement with the LYRA measurements and predictions made by the NRLMSISE‐00 empirical model for Earth's thermospheric density (Picone et al, ), which has been independently characterized and validated by available thermospheric density measurements at the Earth. The good agreement between LYRA solar occultation observations and NRLMSISE‐00 predictions also serve to validate the EUVM‐SO observations given the similarities in the instruments and near identical retrieval algorithms.…”
Section: Density Retrieval Uncertaintymentioning
confidence: 89%
“…A brief description of the retrieval method is summarized here, but the reader is referred to those two papers for a detailed description of the retrieval method. In particular, the study of Thiemann, Dominique, et al () was motivated by an effort to validate methods used in this study by applying them at the Earth, where thermospheric densities are better understood. As such, the method of Thiemann, Dominique, et al () is nearly identical to the method used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations